Evaluación de los principales impactos ambientales del uso del glifosato como agente plaguicida de cultivos ilícitos en zonas rurales del país (2021)
The issue of marijuana, coca and poppy crops classified as illegal has been constantly addressed in recent years; especially in Colombia in the government of President Iván Duque because eradication through aerial spraying with chemical products has been the most used strategy, within a scheme that has been dedicated to attacking mainly the supply of drugs instead of programs to prevent the compulsive consumption, fighting drug traffickers, supplying chemical precursors and laundering dollars that feed the international financial system.